1995
DOI: 10.1111/j.1749-7345.1995.tb00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Protein Concentration on Growth, Survival, and Body Composition of Muskellunge Esox musquinongy and Tiger Muskellunge Esox masquinongy × E. luscius Fingerlings

Abstract: Growth rate, survival and body composition of muskellunge Esox musquinongy (initial mean total length = 125 mm) and tiger muskellunge E. masquinongy × E. lucius (initial mean total length = 115 mm) fed semi‐purified diets differing in protein level from 31 to 40% and 34 to 45%, respectively, were evaluated in 8‐wk trials. The minimum protein level that yielded satisfactory growth rates for muskellunge was 37%, whereas tiger muskellunge growth rates were highest for fish fed a 45% protein diet. Growth differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Generally, F 1 performed better on diets with low CP/CL (46/23, 41/28) than did RSB, providing evidence that F 1 had a lower protein requirement than the female parental fish (RSB). These findings are consistent with those in several other species where hybrid fish ordinarily showed lower protein requirements than the maternal fish (Millikin, 1982(Millikin, , 1983Berger and Halver, 1987;Shiau and Huang, 1989;Tuncer et al, 1990;Brown et al, 1992;Swann et al, 1994;Brecka et al, 1995;Twibell and Brown, 1998). Azevedo et al (2004) found a significant difference in growth between rainbow trout and Atlantic salmon by feeding various CP/CL diets.…”
Section: Trialsupporting
confidence: 89%
See 2 more Smart Citations
“…Generally, F 1 performed better on diets with low CP/CL (46/23, 41/28) than did RSB, providing evidence that F 1 had a lower protein requirement than the female parental fish (RSB). These findings are consistent with those in several other species where hybrid fish ordinarily showed lower protein requirements than the maternal fish (Millikin, 1982(Millikin, , 1983Berger and Halver, 1987;Shiau and Huang, 1989;Tuncer et al, 1990;Brown et al, 1992;Swann et al, 1994;Brecka et al, 1995;Twibell and Brown, 1998). Azevedo et al (2004) found a significant difference in growth between rainbow trout and Atlantic salmon by feeding various CP/CL diets.…”
Section: Trialsupporting
confidence: 89%
“…It is known that some hybrids have similar or different dietary protein and lipid requirements compared with their parents (Brecka et al, 1995;Twibell et al, 2003). Moreover, there are some suggestions that the hybrids showed heterosis in growth, survival and disease tolerance, distinguishable from their parent species (Logan, 1968;Blanc and Chevassus, 1982;Tuncer et al, 1990;Brecka et al, 1995;Moreau and Pauly, 1999;Harel and Place, 2003).…”
Section: Measurements and Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Crosses between different species also resulted in improved environmental and disease tolerances (Dorson, Chevassus, & Torhy, ; Lim, Leamaster, & Brock, ). However, some hybrid offsprings showed lower or no growth rates compared to their parents (Cao et al, ) and some hybridization produced sterile offspring (Brecka, Kohler, & Wahl, ; Galbreath & Thorgaard, ) or only fertile offspring of a single gender.…”
Section: Introductionmentioning
confidence: 99%
“…Currently there are recommendations for minimum protein demand for North American relative species * To whom correspondence should be addressed. Phone: +36-82-505 800; e-mail: kucska.balazs@ke.hu muskellunge (Esox masquinongy) (CP 37%) and tiger muskellunge, its hybrid with pike (E. masquinongy × E. lucius) (45%) (BRECKA et al, 1995), but it has not yet been determined in the case of pike. Moreover, the effect of different protein and energy ratios in feeds has not been studied yet.…”
mentioning
confidence: 99%